Consulting report - Peruvian Traditions SAC - Díaz Montalván, Sarai Abigail (2019)
Peruvian Traditions is a small family business dedicated to the manufacture and export of alpaca garments. Currently, it has two brands White Label (Peruvian Traditions itself) and Norgäte and is aiming to expand its export process to Europe. Within the process of collecting information and analyzing the company, it was detected that the problem was the lack of differentiation between one brand and another which leads them to be "stuck in the middle". As a result, solutions were proposed for the problem determining that offering new product line called Alpaca Basics based on pre-existing garments within the Norgäte collection and on which it has been detected quite welcome, would be the best. The framework for this product line is the lean start-up methodology that is characterized by the formulation of a hypothesis and a testing process under continuous customer feedback that allows reaching a desired market-fit. Based on a previous analysis based on the segmentation, targeting and positioning (STP) the Netherlands was identified as target market. For the success of the product line, a 4P marketing campaign is required: product, place, price and promotion, which highlights the use and improvement of the current Peruvian Traditions website and a Google Ads campaign. To measure the results, three indicators will be used: number of visits through the web, conversion ratio and sales ratio. Subsequently, a scenario analysis is carried out taking into account three perspectives: negative, neutral and positive. Taking the neutral perspective as a reference, an increase in the number of visits is identified, from 1,460 to 4,380 visits per year. Which could generate an increase in the number of customers from 13 to 63.